Students' Understanding of Health and Social Issues: A GEDSI Perspective At Two Islamic Universities in Indonesia - Islamiyatur Rokhmah; Warsiti Warsiti; Ellyda Rizki Wijhati; Dahniar Dahniar (Media Kesehatan Politeknik Kesehatan Makassar, 2026)
The Gender Equality, Disability, and Social Inclusion (GEDSI) framework explicitly seeks to address the structural barriers faced by marginalized groups, yet institutionalizing these frameworks within higher education settings often faces deep implementation gaps. While macro-policies and empirical violations are widely documented, understanding how university students conceptualize these intersecting issues is crucial for developing genuinely responsive campus ecosystems. This study aims to analyze the level of GEDSI understanding among Indonesian university students. An explanatory sequential mixed-methods design was conducted concurrently at Universitas 'Aisyiyah Yogyakarta and Universitas Muhammadiyah Makassar. The quantitative phase utilized a 17-item Likert scale questionnaire administered to 71 purposively sampled undergraduate students from various health and technical programs. Subsequently, the qualitative phase involved semi-structured interviews and focus group discussions with a subset of 15 students selected based on survey score variations. The quantitative data underwent descriptive statistical analysis, while the qualitative audio recordings were transcribed verbatim and examined using thematic analysis. The findings reveal a distinct dualism in how university students conceptualize the GEDSI framework. In the public sphere, students demonstrated progressive perspectives, with 97.2% supporting equal leadership roles for female and 98.6% agreeing that classroom religious differences must be accommodated. Conversely, deeply internalized stereotypes persisted in the domestic domain, with 95.7% maintaining that the role of head of household belongs exclusively to men. Furthermore, despite 100% support for physical campus accessibility, 90.1% of respondents perceived individuals with disabilities through a traditional charity-based model rather than a structural, rights-based framework. A clear divergence persists between students' public endorsement of equity and their internalized, traditional beliefs regarding domestic gender roles and charity-focused models of disability.